汉语二语者写作研究回顾与展望——基于CiteSpace的知识图谱分析 - Wang Lujin (Sinolingua: Journal of Chinese Studies, 2024)
This study uses CiteSpace to analyze research trends in writing for Chinese as a Second Language (CSL) in the CNKI database. The field of CSL writing is currently rapidly evolving. Writing assessment research primarily examines linguistic differentiation features and their predictive ability on writing quality. Writing teaching research encompasses empirical summaries, teaching methods, and teaching materials. The articles explore teaching methods and their effectiveness in practical applications. It also analyzes Chinese learners' writing features and errors from a linguistic perspective. Additionally, it investigates the influencing factors on writing, such as task type, task complexity, and genre. The article concludes by offering insights into future research directions in CSL writing.